2018
DOI: 10.1007/s10811-018-1699-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the cellular matrix of Aphanizomenon strains in the effects of cylindrospermopsin—an experimental study

Abstract: A few literature data suggest that one of the possible roles of the cyanotoxin cylindrospermopsin (CYN) is forcing other phytoplankton species in the environment to produce alkaline phosphatase, which enables the cyanobacterium to take up the enzymatically liberated phosphate. In this study, cultures of a planktonic green alga Scenedesmus obtusus (Chlorophyta, Sphaeropleales) were treated with CYN producer Aphanizomenon (Cyanobacteria, Nostocales) crude extract (C+), with non-CYN producer Aphanizomenon crude e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Exposure of Scenedesmus obtusus to the extracts of CYN-producing and -deficient strains of Aphanizomenon , as well as CYN-deficient extracts supplemented with CYN, showed that only the extracts of the toxic strain-induced alkaline and acidic phosphatases activity in the green alga. These data indicate the presence of other metabolites with similar effects that are absent in the toxin-deficient strain or not contributed to CYN toxicity [ 184 ].…”
Section: Cyanotoxins and Interspecies Interplaymentioning
confidence: 99%
“…Exposure of Scenedesmus obtusus to the extracts of CYN-producing and -deficient strains of Aphanizomenon , as well as CYN-deficient extracts supplemented with CYN, showed that only the extracts of the toxic strain-induced alkaline and acidic phosphatases activity in the green alga. These data indicate the presence of other metabolites with similar effects that are absent in the toxin-deficient strain or not contributed to CYN toxicity [ 184 ].…”
Section: Cyanotoxins and Interspecies Interplaymentioning
confidence: 99%
“…To date, four other naturally occurring analogues have been identified in cyanobacteria: 7-epi-CYN, 7-deoxy-CYN, 7-deoxy-sulfate-CYN, and -deoxy-desulfo-12-CYN [74,75], with CYN being the most toxic. The biological role of CYN is under debate, with experimental studies suggesting its involvement in the acquisition of inorganic phosphate via inducement of alkaline phosphatase in other photosynthetic microalgae [12,76,77]. The biosynthesis of CYN is related to the cyr gene cluster, spanning 43 kb and comprised of 15 open reading frames, containing the genes required for biosynthesis, regulation, and transport of the compound [78].…”
Section: Cylindrospermopsin (Cyn)mentioning
confidence: 99%
“…On the other hand, various metabolites can be actively produced and released by intact cells to acquire available nutrients and sustain growth. For example, it has been suggested that cylindrospermopsin is involved in phosphate acquisition by triggering the release of alkaline phosphatase in other phytoplankton species [34,35]. However, some toxins, such as microcystins, can be released during necrosis and stress-induced programmed cell death to mediate the survival of the remaining cell population under unfavorable conditions [36].…”
Section: Introductionmentioning
confidence: 99%